ANALISA POTENSI KECEPATAN ANGIN PADA MODUL LATIH RANCANG BANGUN PLTB - Monika, Dezetty; Nadhiroh, Nuha; Mutiar, Mutiar (Program Studi Teknik Elektro Fakultas Teknik Universitas Palembang, 2024)
Electrical energy is energy that can be generated from the conversion of various types of energy, one of which is wind energy. The average wind speed in Indonesia is classified as low speed, only certain areas have moderate to high wind speeds. Low wind speed does not mean that the potential energy contained in it cannot be utilized or converted into electrical energy, it can still be utilized but a generator is needed that matches the characteristics of the wind speed. Therefore, the turbine used is the Savonius type, which can work in low wind speeds. The purpose of this research is to measure output power against wind speed. With experimental methods using an anemometer and measuring voltage, current and output power. From the results of this study, the maximum power generated by the wind power training module is 0.008 Watt with a wind speed of 4.31 m/s and the minimum power generated is 0.001 Watt with a wind speed of 1.17 m/s. In a day, the average wind speed is 2.94 m/s so from the wind speed the wind power training module is able to produce an average power of 0.001 Watt.